ANALISIS PERHITUNGAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 21 WAJIB PAJAK ORANG PRIBADI PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KOTA MANADO - Gosal, Yeremia; Karamoy, Herman; Warongan, Jessy (Universitas Sam Ratulangi, 2017)
This study aims to determine the calculation and reporting of income tax article 21 permanent employee at the Regional Finance and Asset Management Board (BPK-AD) Manado City and comparing with the Minister of Finance Regulation no. 101 / PMK.010/2016 and Regulation of the Director General of Taxation Number: PER - 31 / PJ / 2012. Non-Taxable Income (PTKP) is a deduction in the calculation of income tax article 21. As for the increase of PTKP this causes the tax burden becomes even less zero, for individual taxpayer. The research method used is qualitative research using interview technique and documentation observation. Next describe the data received and present it in accordance with the actual situation. The result of the research shows that the calculation of Income Tax Article 21 individual taxpayer by BPK-AD of Manado City is not in accordance with Law Number 36 Year 2008 because the amount inputted has excess number which can cause Income Tax 21 increased; The determination of non-taxable income (PTKP) is in conformity with Regulation of the Minister of Finance no. 101 /PMK.010/2016; The reporting of PPh 21 employees, conducted through e-filling at the latest end of April, but not in accordance with tax regulations. Keywords: Calculation, Reporting, and Income Tax Article 21